Pelatihan Pembuatan Modul Ajar Inovatif Sesuai Tuntutan Kurikulum Merdeka di Desa Serdang - Situmorang, Adi Suarman; Br Sinaga, Juli Antasari; Sihombing, Dame Ifa; Sauduran, Golda Novatrasio (Indra Institute Research & Publication, 2023)
This community service activity aims to train teachers in Serdang village, Beringin sub-district in designing innovative teaching modules according to the demands of the independent curriculum, which will be implemented in October-November 2023 with partners as the principal of SD Negeri 101917 and the head of Serdang village, Beringin sub-district, Deli district. Serdang. The location of the activity was held at the Serdang Village meeting office with a capacity of 80 participants. The results of the activities obtained from observations show that the overall achievement of the goals that have been set appears to be in the